Orthopaedic surgery in patients with von Willebrand disease. (28th August 2013) - Siboni, S. M.; Biguzzi, E.; Solimeno, L. P.; Pasta, G.; Mistretta, C.; Mannucci, P. M.; Peyvandi, F.
Summary Patients with von Willebrand disease (VWD) may need orthopaedic surgery because of disabling chronic arthropathy due to recurrent joint bleeding. They may also require this surgery independently of their haemostasis disorder. Knowledge regarding the management of orthopaedic surgery in VWD is limited. Description of management of orthopaedic surgery in patients with VWD, based upon retrospective data collection and analysis of 32 orthopaedic procedures carried out over a period of 33 years in 23 patients was the aim of this study. Of 32 procedures, six were minor (three hand surgery, one foot surgery, two others) and 26 were major (seven joint replacements, nine arthroscopic procedures, two foot surgery, eight others). Twenty‐two procedures were performed using replacement therapy with plasma‐derived concentrates containing both factor VIII (FVIII) and von Willebrand factor (VWF). Two procedures in patients with acquired von Willebrand syndrome (AWVS) were performed using FVIII‐VWF concentrates associated with intravenous immunoglobulins, or desmopressin plus tranexamic acid. Seven procedures were performed using desmopressin alone and one using intravenous immunoglobulins in AVWS. Bleeding complications occurred in seven procedures (22%). In one patient, an anti‐VWF antibody was diagnosed after surgery. Anticoagulant prophylaxis of venous thromboembolism was implemented in four cases only and in two instances there was excessive bleeding. In conclusion, control of surgical haemostasis was achieved in most patients with VWD undergoing orthopaedic surgery. The control of haemostasis combined with an adequate surgical technique and early post‐operative rehabilitation are warranted for the successful performance of orthopaedic surgery in VWD, which requires the involvement of specialized haemophilia centres.